5 Terobosan dahsyat menyulap si kecil jadi luar biasa / Imam Ahmad Ibnu Nizar ; editor Zainul Arifin El - Basyier - Nizar , Imam Ahmad Ibnu; El - Basyier , Zainul Arifin (Garailmu, 2009)
198 hlm 20 cm